APPLICATION OF THE DISCOVERY LEARNING MODEL TO THE THEMATIC LEARNING RESULTS OF CLASS V STUDENT’S AT SETIA MARGA ELEMENTARY SCHOOL - Ice Trisnawati; Aren Frima; Tio Gusti Satria (Yayasan Citra Dharma Cindekia, 2020)
This study aims to determine the completeness of the Thematic learning outcomes of grade V Elementary School Of Setia Marga after the application of the Discovery Learning. This research method uses quasi-experimental research methods. Data collection was done by using test techniques. The data collected were analyzed using the t-test at the significant level ? = 0.05, obtained tcount = 2.12> ttable = 1.73, so it can be concluded that the thematic learning outcomes of the VC class students Elementary School of Setia Marga after the application of the Discovery Learning model significantly complete with an average student learning outcomes of 78.15.